Impact of acute sodium citrate ingestion on endurance running performance in a warm environment - Vaher, I.; Timpmann, S.; Aedma, M.; Ööpik, V. (European Journal of Applied Physiology, 2015)
Purpose: Dietary supplements inducing alkalosis have been shown to be ergogenic during intense endurance exercise in temperate environments, but there is lack of data regarding the efficacy of these substances in the heat. This study aimed to investigate the effect of sodium citrate (CIT) ingestion on 5,000-m running performance in a warm environment.